Preferences for health insurance in Germany and the Netherlands: A tale of two countries - Karolin Leukert-Becker; Peter Zweifel (Health Economics Review, 2014)
Background: This contribution seeks to measure preferences for health insurance in Germany and the Netherlands, using two Discrete Choice Experiments (DCE). Since the Dutch DCE was carried out right after the 2006 health reform, which made citizens explicitly choose a health insurance contract, two research questions naturally arise. First, are the preferences with regard to contract attributes (such as Managed Care-type restrictions of physician choice), incentives (such as bonus options for no claims, deductibles, and a bonus for preventive behavior), and extra services provided by the health insurer (such as patient counseling) similar between the two countries? Second, was the requirement to explicitly choose imposed by the Dutch government in the context of the reform effective in reducing status quo bias with respect to future reforms? Results: Based on random-effects Probit estimates, these two questions can be answered as follows. First, there is resistance against Managed Care-type attributes in both populations, but Germans would have to be compensated more for giving up free physician choice. Second, their status quo bias is twice as important as among their Dutch counterparts, who apparently learned to bear the cost of information associated with future choices concerning their health insurance.
Keywords: C25; D12; I18; 330; Preference measurement; Health insurance; Discrete choice experiments; Health reform; Germany; Netherlands